Seeing double? A practice-based investigation into twins experiences of sporting talent development - Taylor, R. D.; Carson, H. J.; Collins, D. (International Sport Coaching Journal, 2021)
Although there is an established body of research on twins within the wider social science domain, scarce attention has been applied to this relationship within sport coaching practice. Specifically, this is apparent during talent development, despite a growing empirical interest toward the developmental impact of age-gapped siblings on sporting success. Accordingly, this study explored potential mechanisms through which the twin relationship may impact on talent development. Longitudinal observation of two twin sets (one monozygotic and one dizygotic) took place within a U.K. regional hockey performance center training environment. Observations were used to inform semistructured interviews with twins and their parents, which facilitated the interpretation of observations and exploration of the relationship, before a codebook thematic analysis was conducted. Findings revealed several themes (regularity of interaction, emotional interpersonal skills, rivalry, skill development, communication, and type of separation) consistent with previous studies, alongside two new themes; namely, conflict and identity. The study highlights the complex and individualized nature of the sibling subsystem, illuminating the possible impact of twin type on several themes, and highlights the potential for observations as a practice-based tool for coaches to consider when individualizing the talent development process.